The extent of the glandular resection in the differentiated carcinoma of the thyroid - Delgado, Bolívar (Cirugía del Uruguay, 1990)
The author ana/yses the problem of the extension of glandular resection in differentiated carcinoma of the thyroid and based on bibliographical revision and results of a series of 39 resected carcinomas of this type, suggests that the selection of tha surgical tactic should be made by schematizing the situations that, according to extension of glandular resection, correspond to total lobectomy, total thyroidectomy, and near-total thyroidectomy, with a clear predominance of the last procedure.